New technology for recovering residual metals from nonmetallic fractions of waste printed circuit boards. (June 2017) - Zhang, Guangwen; He, Yaqun; Wang, Haifeng; Zhang, Tao; Wang, Shuai; Yang, Xing; Xia, Wencheng
Graphical abstract: Highlights: Vibrated gas-solid fluidized bed can recycle residual metals from WPCBs. Glass fibers have bad effect on vibrated gas-solid fluidized bed segregation. Each size fraction has its own optimum segregation parameters. Fine size fraction has the worst segregation efficiency. Abstract: Recycling of waste printed circuit boards is important for environmental protection and sustainable resource utilization. Corona electrostatic separation has been widely used to recycle metals from waste printed circuit boards, but it has poor separation efficiency for finer sized fractions. In this study, a new process of vibrated gas-solid fluidized bed was used to recycle residual metals from nonmetallic fractions, which were treated using the corona electrostatic separation technology. The effects of three main parameters, i.e., vibration frequency, superficial air flow velocity, and fluidizing time on gravity segregation, were investigated using a vibrating gas-solid fluidized bed. Each size fraction had its own optimum parameters. Corresponding to their optimal segregation performance, the products from each experiment were analyzed using an X-ray fluorescence (XRF) and a scanning electron microscope (SEM) equipped with an energy dispersive spectrometer (EDS). From the results, it can be seen that the metal recoveries of −1 + 0.5 mm, −0.5 + 0.25 mm, and −0.25 mm size fractions were 86.39%, 82.22% and 76.63%, respectively. After separation, each metal content in the −1 + 0.5 or −0.5 + 0.25 mm size fraction reduced to 1% or less, while the Fe and Cu contents are up to 2.57% and 1.50%, respectively, in the −0.25 mm size fraction. Images of the nonmetallic fractions with a size of −0.25 mm indicated that a considerable amount of clavate glass fibers existed in these nonmetallic fractions, which may explain why fine particles had the poorest segregation performance.